2016
DOI: 10.1016/j.chembiol.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Redox Activation of Epidermal Growth Factor Receptor Kinase

Abstract: SUMMARY EGFR is a target of signal-derived H2O2 and oxidation of active site cysteine 797 to sulfenic acid enhances kinase activity. Although a major class of covalent drugs targets C797, nothing is known about its catalytic importance or how S-sulfenylation leads to activation. Here, we report the first detailed functional analysis of C797. In contrast to prior assumptions, mutation of C797 diminishes catalytic efficiency in vitro and cells. The experimentally determined pKa and reactivity of C797 towards H2O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(136 citation statements)
references
References 66 publications
5
128
3
Order By: Relevance
“…Thus, the joining of components of dedicated signaling networks together by microdomains might represent one way in which nearby effectors are modified and signals are passed from the ROS source in a concentration-dependent gradient. This model is in agreement with the recent discovery of oxidative PTMs of intracellular domains of cell surface receptors in animals (Truong et al, 2016). Conceptually, the hypothesis of local ROS maxima is well established, but the proposed model does not provide a sufficient explanation for the problem of differentiation between intracellular and apoplastic ROS sources.…”
Section: Intracellular Sensing Of Apoplastic Rossupporting
confidence: 77%
“…Thus, the joining of components of dedicated signaling networks together by microdomains might represent one way in which nearby effectors are modified and signals are passed from the ROS source in a concentration-dependent gradient. This model is in agreement with the recent discovery of oxidative PTMs of intracellular domains of cell surface receptors in animals (Truong et al, 2016). Conceptually, the hypothesis of local ROS maxima is well established, but the proposed model does not provide a sufficient explanation for the problem of differentiation between intracellular and apoplastic ROS sources.…”
Section: Intracellular Sensing Of Apoplastic Rossupporting
confidence: 77%
“…This could have direct consequences for EGFR signaling as it is highly subject to redox regulation. Indeed, various recent studies indicated that oxidation of a conserved cysteine near the ATP-binding site within the EGFR tyrosine kinase domain, C797, is susceptible to oxidation, and research by Kate Carroll and co-workers has indicated that oxidation of EGFR C797 to a sulfenic acid (−SOH) in response to ligand stimulation contributes to enhanced tyrosine kinase activity [236238]. Moreover, the extent of EGFR C797 oxidation varied between cancer cells with WT EGFR or containing oncogenic mutants (e.g.…”
Section: Duox1 Silencing Emt and Altered Egfr Dynamics: A Dangerousmentioning
confidence: 99%
“…In addition to oxidation to −SOH, our recent studies show that EGFR is also subject to S -glutathionylation, which may not necessarily affect kinase activity [134, 148, 239] but likely impact on the efficacy of EGFR TKI that are covalently targeted to C797 in an attempt to overcome TKI resistance[238, 240, 241]. Although oxidation of EGFR C797 to −SOH may enhance tyrosine kinase activity [148, 238], the significance of other modifications (e.g. S -glutathionylation) for EGFR regulation is unknown, and it is plausible that these redox modifications might also affect subcellular EGFR trafficking.…”
Section: Duox1 Silencing Emt and Altered Egfr Dynamics: A Dangerousmentioning
confidence: 99%
“…In fact, the “concentrations” of H 2 O 2 or a given protein target within a signaling complex is impossible to define without knowledge of the “volume” in which H 2 O 2 is allowed to diffuse, but are likely much greater than estimated cellular concentrations of specific proteins, or even the highest estimates of steady-state cellular H 2 O 2 concentrations (e.g. [24]), and will enable even kinetically less favorable reactions.…”
Section: Reaction Of H2o2 With Thiol Proteins: Reaction Kinetics Vmentioning
confidence: 99%
“…Since intermediate formation of Cys-SOH is being recognized as a functionally critically intermediate in redox-dependent regulation of e.g. tyrosine kinases [24, 25], it is important to reconcile this issue. In the following paragraphs, we will briefly discuss some of the concerns regarding the selectivity of certain derivatization strategies [26, 27], and point out important considerations with respect to extrapolating experimental findings from biochemical kinetic studies with isolated proteins conducted in the test tube to intact cellular contexts.…”
Section: Introductionmentioning
confidence: 99%